2019
DOI: 10.1186/s11671-019-3015-x
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-level Memristor Based on Al-Doped HfO2 Thin Film

Abstract: Non-volatile memory (NVM) will play a very important role in the next-generation digital technologies, including the Internet of things. The metal-oxide memristors, especially based on HfO 2 , have been favored by lots of researchers because of its simple structure, high integration, fast operation speed, low power consumption, and high compatibility with advanced (complementary metal oxide silicon) CMOS technologies. In this paper, a 20-level stable resistance states Al-doped HfO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 38 publications
1
31
0
1
Order By: Relevance
“…A clear state difference is observed for the CB case, where LRS values are below 100 Ω and HRS values are in the range of 1–10 kΩ. These values are similar to the ones reported for sputtered Hf oxide memristors, but here the HRS/LRS ratio is slightly higher, exceeding one order of magnitude [ 44 , 45 ].…”
Section: Resultssupporting
confidence: 81%
“…A clear state difference is observed for the CB case, where LRS values are below 100 Ω and HRS values are in the range of 1–10 kΩ. These values are similar to the ones reported for sputtered Hf oxide memristors, but here the HRS/LRS ratio is slightly higher, exceeding one order of magnitude [ 44 , 45 ].…”
Section: Resultssupporting
confidence: 81%
“…Multi-level resistance states depending on the SET current compliance (I cc ) were investigated to find the influence of increasing oxygen vacancy concentration inside conducting filaments (CF) [ 36 , 37 , 38 ]. Figure 5 a shows the resistive switching characteristics with variable I cc during the SET process from 100 µA to 1 mA.…”
Section: Resultsmentioning
confidence: 99%
“…Several works have shown that memristor devices can exhibit stable multi-level resistance states that are captured in the device models [38], [39]. Authors in [40] fabricated a Al-doped HfO 2 -based memristor with 20-levels. Also in [41] reported on a 12-levels stable resistance states using HfO 2−x .…”
Section: Proposed Work-flow For Reram-based Neural Network Inferencementioning
confidence: 99%